Agricultural Water Quota Evaluation in Guizhou Province of China - ZHENG Jiangli; LI Xingpin; ZHANG Kang; WANG Sen (Renmin Zhujiang)
Quota management is a basic system for water resource management stipulated by the water law.On the basis of the technical requirements of water quota evaluation,the evaluation index system for agricultural water quota in Guizhou Province is established.Each index is quantified,and evaluation standards are put forward.The evaluation results show that:① The evaluation value of agricultural water quota coverage in Guizhou Province is 96.9%,which indicates that the coverage is “strict.” ② The rationality evaluation value of the agricultural water quota in Guizhou Province is 85%,and thus the classification result is “reasonable.” ③ Guizhou agricultural water quota has been applied in agricultural water management and related planning.The satisfaction rate of the practicability evaluation of the agricultural water quota is100%,and thus the practicability evaluation conclusion is “strict.” ④ The comprehensive deviation degree of Guizhou agricultural water quota from the water quota of agricultural irrigation water in adjacent Yunnan,Chongqing,Hunan,Sichuan,and Guangxi is -30.07%,and thus the advancement evaluation conclusion is “strict.” The evaluation results can provide support for agricultural water management in Guizhou Province or southwest China.